1998
DOI: 10.1172/jci639
|View full text |Cite
|
Sign up to set email alerts
|

Polyvariant mutant cystic fibrosis transmembrane conductance regulator genes. The polymorphic (Tg)m locus explains the partial penetrance of the T5 polymorphism as a disease mutation.

Abstract: In congenital bilateral absence of the vas deferens patients, the T5 allele at the polymorphic Tn locus in the CFTR (cystic fibrosis transmembrane conductance regulator) gene is a frequent disease mutation with incomplete penetrance. This T5 allele will result in a high proportion of CFTR transcripts that lack exon 9, whose translation products will not contribute to apical chloride channel activity. Besides the polymorphic Tn locus, more than 120 polymorphisms have been described in the CFTR gene. We hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
322
6
12

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 375 publications
(357 citation statements)
references
References 43 publications
17
322
6
12
Order By: Relevance
“…Previous studies suggested that IVS8-5T shows higher disease penetrance when it is combined with the higher number of IVS8-(TG)m. 15 It was found that 5T was in cis with three different TG repeats (TG11-5T, TG12-5T, TG13-5T). 13 In 72 cases with 97 alleles of IVS8-5T present in 109 Chinese CBAVD patients, 70 cases (97.22%) and 94 alleles (96.91%) had 12 or 13 TG repeats adjacent to 5T.…”
Section: Cftr Polymorphisms In Chinese Males With Cbavd Wh Ni Et Al 688mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies suggested that IVS8-5T shows higher disease penetrance when it is combined with the higher number of IVS8-(TG)m. 15 It was found that 5T was in cis with three different TG repeats (TG11-5T, TG12-5T, TG13-5T). 13 In 72 cases with 97 alleles of IVS8-5T present in 109 Chinese CBAVD patients, 70 cases (97.22%) and 94 alleles (96.91%) had 12 or 13 TG repeats adjacent to 5T.…”
Section: Cftr Polymorphisms In Chinese Males With Cbavd Wh Ni Et Al 688mentioning
confidence: 99%
“…14 Another common variant in CFTR, a methionine or valine at codon 470, was suggested to influence the penetrance of 5T. 15 The quantity and quality of CFTR transcripts and/or proteins was affected by (TG)m(T)n and M470V polymorphic loci. 15 Previous studies have demonstrated that the 5T-V470 haplotype showed a higher disease association than the 5T-M470 haplotype.…”
Section: Cftr Polymorphisms In Chinese Males With Cbavd Wh Ni Et Al 688mentioning
confidence: 99%
See 3 more Smart Citations